Climate and Energy in Urban Areas to Reduce Energy Consumption, Case Study of Saadat Abad Building - pariz Amiri Ade; Saeed Tizghalam zenozi; Mehrdad Javidi Nejad (تحقیقات کاربردی علوم جغرافیایی)
Before the modern era, cities were built on a scale that did not change the environmental balance significantly. With the expansion of population and the expansion of cities and the conversion of settlements into big cities and metropolises, new conditions have emerged which show that cities today make their own climates. The new climates created in these areas are completely different from their predecessors. In this study, we try to use urban and architectural solutions in the Saadat Abad area of ​​Tehran to reduce energy consumption. Urban and architectural variables including street and sidewalk width, green space and trees, materials, dimensions and directions for openings and energy entry paths, roof, wall width, porch, passive heating control (canopies, curtains and systems) Pore ​​controls). So first, we examined the climate and climate of Tehran and Saadat Abad. Then, model the current status of Saadat Abad using simulated software to evaluate ambient and building temperature. The results of the study showed that improvement of outdoor thermal conditions and bio-closure of residential buildings. Reduction of direct and indirect thermal energy loss through exterior shell of buildings. Upgrading of the exterior shell climatic design knowledge of the building on the southern flank of central Alborz mountain range of Tehran.